2006
DOI: 10.1099/mic.0.28293-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the glucose-specific phosphoenolpyruvate : sugar phosphotransferase system from Lactobacillus casei and its links with the control of sugar metabolism

Abstract: Lactobacillus casei transports glucose preferentially by a mannose-class phosphoenolpyruvate : sugar phosphotransferase system (PTS). The genomic analysis of L. casei allowed the authors to find a gene cluster (manLMNO) encoding the IIAB (manL), IIC (manM) and IID (manN) proteins of a mannose-class PTS, and a putative 121 aa protein of unknown function (encoded by manO), homologues of which are also present in man clusters that encode glucose/mannose transporters in other Gram-positive bacteria. The L. casei m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…The specificity of the Mpt PTS has not been determined, but it is likely to be the mannose/glucose-specific PTS, as its expression in L. monocytogenes is induced by these two sugars (151). In addition, the EIID domain of the Mpt PTS possesses a C-terminal extension characteristic of mannose/glucose-specific PTS, and the various sugar-specific EII Mpt components exhibit the strongest similarity to those of the recently characterized mannose/glucose PTS of L. casei (975). Homologs of the Mpt PTS are present in E. faecalis and Listeria innocua, and the absence of expression of the mpt operon in these organisms also leads to resistance towards class IIa bacteriocins such as mesentericin Y105 for E. faecalis (320) and pediocin AcH for L. innocua (959).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the Mpt PTS has not been determined, but it is likely to be the mannose/glucose-specific PTS, as its expression in L. monocytogenes is induced by these two sugars (151). In addition, the EIID domain of the Mpt PTS possesses a C-terminal extension characteristic of mannose/glucose-specific PTS, and the various sugar-specific EII Mpt components exhibit the strongest similarity to those of the recently characterized mannose/glucose PTS of L. casei (975). Homologs of the Mpt PTS are present in E. faecalis and Listeria innocua, and the absence of expression of the mpt operon in these organisms also leads to resistance towards class IIa bacteriocins such as mesentericin Y105 for E. faecalis (320) and pediocin AcH for L. innocua (959).…”
Section: Discussionmentioning
confidence: 99%
“…casei is a facultative heterofermentative lactic acid bacterium frequently used as a cheese starter culture and which is also employed as a probiotic. Extensive research has been carried out on the study of sugar catabolism (28,(39)(40)(41); however, the knowledge of the utilization of organic acids has received less attention. As previously indicated, physiological and biochemical studies identified two L-malate dissimilation pathways in L. casei.…”
mentioning
confidence: 99%
“…These results, together with the lack of transcription during growth on rapidly metabolized substrates (glucose and sucrose), suggest that regulation of the sim operon is mediated via carbon catabolite repression. This mode of regulation of catabolic operons, particularly those involved in the dissimilation of sugars, is found in many species of gram-positive bacteria, including strains of L. casei (7,18,41,45). It is likely that the CRE region is the target for a multicomponent complex (phosphorylated disaccharide, catabolite control protein A [CcpA], and phospho-seryl-HPr) that modulates expression of the sim operon in L. casei ATCC 334.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these interactive proteins constitute a fivestage phosphorelay that, via transfer of the high-energy phosphoryl moiety from PEP, catalyzes the simultaneous phosphorylation and translocation of sugars through the cytoplasmic membrane. Biochemical and physiological studies performed during the past 25 years have established the presence of a variety of sugar PEP-dependent PTSs in L. casei, including PTSs for glucose (41,45), galactose (2,6), lactose (4,5,8,9), sorbose (46), and pentitols (15,16). Significantly, in the past decade, the development and application of techniques for manipulation of LAB genomes have provided extensive (and in some instances unexpected) insight into the molecular basis for regulation of PEP-dependent PTSs in L. casei (18,42,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation